Peanut skin phenolics obtained by green solvent extraction: characterization and antioxidant activity in pure chia oil and chia oil in water (O/W) emulsion. (22nd October 2021) - Bodoira, Romina; Martínez, Marcela; Velez, Alexis; Cittadini, Maria C; Ribotta, Pablo; Maestri, Damián
Abstract: BACKGROUND: The peanut skin (PS) is considered as an industrial waste with undervalued applications. Although several studies report potent antioxidant capacities of PS phenolics, the effectiveness in highly unsaturated lipid systems has not yet been evaluated. The objectives of the present study were two‐fold: (i) to characterize a PS phenolic extract (PSE) obtained by means of a green technology and (ii) to evaluate its antioxidant efficacy on pure chia oil and chia oil in water ( O/W) acid emulsion. RESULTS: PSE was composed mainly of monomeric and condensed flavonoids (procyanidin and proanthocyanidin oligomers). PSE displayed strong antioxidant properties as measured by different reducing power and radical scavenging capacities [IC50 = 0.36 μg dry extract (DE) mL −1 for ferric reducing antioxidant power; IC50 = 4.96 μg DE mL −1 for 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) ; IC50 = 6.01 μg DE mL −1 for 2, 2′‐azinobis‐3‐ethylbenzothiazoline‐6‐sulfonic acid (ABTS) + ; IC50 = 2.62 μg DE mL −1 for HO ]. It also showed high antioxidant efficacy when tested in pure chia oil under accelerated oxidation conditions (Rancimat, 100 °C). When added to the O/W emulsions maintained at 40 °C for 15 days, the PSE was more effective than a synthetic antioxidant (tert‐butylhydroquinone) with respect to minimizing the formation and degradation of lipid hydroperoxides. CONCLUSIONS: The antioxidant efficacy of PSE was primarily attributed to the abundance of compounds with a high number of phenolic‐OH groups. Because they were found to cover a relatively wide range of partition coefficients, the antioxidant properties could be also enhanced by effect of both interfacial and solubility phenomena. All of these features allow the potential use of PSE as a natural antioxidant in different types of foods, including acid emulsion systems. © 2021 Society of Chemical Industry.